THE ROLE OF SINGLE PARENT IN EDUCATING CHILDREN'S RELIGION: (Case Study in Sawahan Hamlet) - Bahiroh, Siti (Transpublika Publisher, 2024)
For single parents, their tasks and responsibilities are so extensive. They have multiple roles in assisting children alone. This study aims at finding out how single parents give their children a religious education. The subjects of the research are 8 single parents situated in Sawahan hamlet. In this study, the researcher utilized a qualitative approach with interview, observation, and documentation methods. Moreover, the data analysis methods were descriptive analytics and triangulation. The study findings reveal that single parents in Sawahan hamlet offer guidance on religious matters, emphasizing politeness and fostering a spirit of mutual assistance. Additionally, they impart socialization skills to their children, facilitating their integration into society. Various educational approaches are employed by single parents, including setting examples, modeling behavior, instilling habits, repetition, and motivation. Challenges encountered by single parents encompass suboptimal child care due to the absence of a spouse, insufficient support and encouragement from relatives, and the burden of sole responsibility for meeting economic needs.